" The ideology of forms in Langston Hughes’s poetry " - (:unkn) unknown (My University, 2003)
The African-American poet Langston Hughes (1902-1967) has produced a considerable poetic œuvre from the beginning of the 1920s to his death in 1967. Taking part in the aesthetic moment of the Harlem Renaissance, he stands out, along with Sterling Brown (1901-1989) and Zora Neale Hurston (1891-1960), by defending African-American folklore and dialect against the upholders of a British tradition of making verse such as Countee Cullen (1903-1946) and Claude McKay (1890-1948). In the collections entitled The Weary Blues (1926) and Fine Clothes to the Jew (1927), Hughes draws his inspiration from the rhythms of blues and jazz music to write his poems which make him the mouthpiece of the Black people. Thus the anti-authority ideology of his work is inscribed in his formal choices as much as in the very content of the poems which is barely disturbing at the time. Contrary to what he did in the 1920s, the poet uses a certain number of languages alien to poetry such as political tracts or advertisements as a means of Bolshevik propaganda in the 1940s. This militant period marks his estrangement from the Harlem Renaissance and a preference for periodical publications to poetry collections so as to react to current events more promptly. With the great polyphonic collections entitled Montage of a Dream Deferred (1951) and Ask Your Mama: 12 Moods for Jazz (1961), the poet revives the musical experimentations of the 1920s, but in a more complex manner, inherited from Modernist techniques. Each collection is conceived as a great poem in which multiple voices cross one another, giving a polemical picture of the history of African-Americans. The influence of Hughes’s formal research on other poets is undeniable, especially in the musical field. For instance, Jack Kerouac (1922-1969), Robert Hayden (1913-1980) and Michael Harper (1938-) owe Hughes their attempt at annexing the rhythms of African-American popular music to the poetic territory.
Keywords: African Research